2019
DOI: 10.1177/1098611119828038
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in Blue: An Analysis of the Extent and Primary Predictors of Burnout Among Law Enforcement Officers in the United States

Abstract: Job-related burnout is a significant concern for researchers, law enforcement administrators, and government authorities because of its broader effects on officer health, job performance, and service provided to the public. This topic is particularly relevant amidst a variety of complex challenges and heightened scrutiny surrounding law enforcement officers, their decisions, and relations with the public. Although much work has been conducted on burnout among police officers, the aim of this study is to build … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 36 publications
(57 reference statements)
4
64
1
3
Order By: Relevance
“…However, the analysis of cut-off points revealed that 11% of the sample presented critical values for Burnout, while values between 9 and 11% were found for other burnout dimensions. These values are less than those found by McCarty et al (2019) who found that 19% of a sample of American police officers suffered with emotional exhaustion and 13% with depersonalization. However, Gutshall et al (2017) found moderate burnout levels for American police officers, whereas Solana et al (2013) found high levels of burnout for Spanish police officers.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…However, the analysis of cut-off points revealed that 11% of the sample presented critical values for Burnout, while values between 9 and 11% were found for other burnout dimensions. These values are less than those found by McCarty et al (2019) who found that 19% of a sample of American police officers suffered with emotional exhaustion and 13% with depersonalization. However, Gutshall et al (2017) found moderate burnout levels for American police officers, whereas Solana et al (2013) found high levels of burnout for Spanish police officers.…”
Section: Discussioncontrasting
confidence: 65%
“…However, a more detailed analysis (Figure 3) revealed that 28 studies sampled 11-95 participants, 24 studies sampled 101-289, 20 studies sampled 305-489, 22 studies sampled 500-951, and 13 studies sampled 1000-4500 participants. One study collected data from 13,146 police officers in the USA (McCarty et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Police officers are a group particularly vulnerable to psychopathological disturbances, which leads them to suffer from burnout and affects their quality of life [ 21 , 27 ]. Previous studies show that police officers involved in life-threatening situations, extreme violence, critical incidents, shootings, hostage or negotiation situations, intense exposure to crime scenes, or coworkers’ death or suicide, can develop burnout syndrome associated with mental health problems [ 5 , 24 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that numerous studies have been conducted on the analysis of burnout in police officers worldwide [ 31 , 33 , 35 , 36 , 37 ], in Mexico there are very few studies related to police officers’ psychopathologies that affect their performance, how these affects relate to their particular conditions and how they correlate with their personal profile and life style related to physical and recreational activities, even more so considering that now there is an obligation for institutions to watch for employees’ psychosocial risks as the new regulation is enforced in Mexican law. Previous studies show that relationships between physical activity, stress, and burnout have received limited attention.…”
Section: Introductionmentioning
confidence: 99%
“…Additional sources of validity evidence, including analyses based on convergent and discriminant evidence, will be helpful in situating police self-efficacy for working with individuals with ASD among other constructs. For example, stress and burnout, two outcomes that are readily examined in policing (e.g., Anshel, 2000;Burke, 1993;McCarty, Aldirawi, Dewald, & Palacios, 2019), have been studied alongside self-efficacy in other occupational spheres.…”
Section: Summary Of Future Researchmentioning
confidence: 99%